Desert Locust Stopped by Tibetan Highlands during the 2020 Upsurge - Jun Liu; Michel Lecoq; Long Zhang (Agronomy, 2021)
Desert locust is an important pest to agriculture. In 2019–2020, a major upsurge originated in the southern Arabian Peninsula and gradually spread to east Africa, then to south-west Asia, as far as Pakistan and India, even reaching Nepal, resulting in major agricultural losses. For the first time, a few swarms entered southern Tibet. Using field observations and experiments, we studied their path to the Tibetan plateau and their behavior at these very high altitudes. The locusts moved up the Tibetan valleys from low-lying areas (1700 m) to much higher elevations (5400 m). The low temperatures and high humidity put them under severe stress; their activities were limited, and they did not survive long or produce local offspring. It is clear that the high-altitude environmental conditions in the Himalayan mountains provided an important natural barrier that limited the northward expansion of the desert locust populations.